Synthesis of silver nanoparticles from Turbinaria ornata and its antibacterial activity against water contaminating bacteria - Anuluxan, S.; Thavaranjit, A.C.; Prabagar, S.; Chinthaka L. De Silva, R.; Prabagar, J. (ResearchGate, 2022)
Advancement of environmentally friendly synthetic methods of nanoparticles is growing in the field of nanotechnology. Turbinaria ornata is a brown alga which is highly abundant in coastal region of Sri Lanka and an excellent source of bioactive compounds. The aim of this study is to synthesise silver nanoparticles (AgNPs) with Turbinaria ornata to use in antibacterial activities. Sources contain Ag nanoparticles are being used for various applications such as photocatalytic degradation and antimicrobial activities. The parameters such as temperature and concentration of the silver nitrate and pH were chosen to find the efficient synthesis of AgNPs. Extracts were prepared at 70 °C was added with 1, 2, 3, 4 and 5 mM AgNO3 and incubated for 24 h at different pHs to prepare the AgNPs. The synthesised nanoparticles were characterized by the surface plasmon resonance band at 430 nm. Highest absorbance band for nanoparticles synthesised from algal extract was obtained at 70 °C and 5 mM silver nitrate at pH 11. The characteristic bands at 3300.93, 2107.30, 1640.74 and 1051.32 cm− 1 in FT-IR suggested that the distinct functional groups, O–H, N–H and C = C are responsible for the reduction and capping of AgNPs. The synthesised nanoparticles were also characterized with X-ray diffraction, energy-dispersive X-ray spectroscopy and scanning electron microscopy. The X-ray diffraction study revealed the average size of the nanoparticles was 8.15 nm obtained at pH 7, 51.11 nm at pH 9 and 40.64 nm at pH 11 and the peaks confirmed the face-centred crystalline lattice of the AgNPs. AgNPs were further confirmed by EDX and SEM images. The synthesised nanoparticles were tested with gram positive Staphylococcus aureus, Enterococcus faecalis and Bacillus circulans and gram-negative Escherichia coli and Pseudomonas aeruginosa. The extract with AgNPs showed the highest antibacterial activity against Staphylococcus aureus. Hence, the AgNPs from Turbinaria ornate was facile and innocuous synthesis which can serve as efficient antimicrobial agent against human pathogens as well as water contaminating bacteria.
Keywords: Antibacterial activity; Characterization; Plant mediated synthesis; Silver nanoparticles; Turbinaria ornata